The relationship between working memory capacity and cortical activity during performance of a novel motor task. (January 2016) - Buszard, Tim; Farrow, Damian; Zhu, Frank F.; Masters, Rich S.W.
Abstract: Objectives: This study assessed whether individual differences in working memory capacity influenced verbal-analytical processes when performing a novel motor skill. Design: Participants performed a tennis-hitting task in two conditions: no pressure and high-pressure. Methods: Eighteen young adults participated in the study. EEG coherence between the T3-F3 and T4-F4 regions in the Beta1 and Alpha2 frequencies was recorded during performance in each condition. Verbal and visuo-spatial working memory capacity were assessed using the Automated Working Memory Assessment. Results: No differences were found between the two conditions for hitting performance and EEG activity. However, across both conditions, verbal and visuo-spatial working memory were significant predictors of EEG coherence between the T3-F3 and T4-F4 regions in the Beta1 and Alpha2 frequencies. Larger verbal working memory capacity was associated with greater coherence while the opposite trend was observed for visuo-spatial working memory capacity. Conclusions: These results indicate that larger verbal working memory capacity is associated with a greater tendency to use explicit processes during motor performance, whereas larger visuo-spatial working memory capacity is associated more with implicit processes. The findings are discussed with relevance to the theory of implicit motor learning. Highlights: Examined EEG coherence in the Beta1 and Alpha2 frequencies during motor performance. Larger verbal WMC was associated with greater T3-F3 coherence. Verbal working memory was therefore linked with explicit processes. Larger visuo-spatial WMC was associated with reduced T3-F3 coherence. Visuo-spatial working memory was theorized to facilitate implicit processes.